Analisis Pertumbuhan Garut (Marantha arundinaceae) Pada Beberapa Tingkat Naungan - Supriyono Supriyono; Retno Bandriyati Arni Putri; Riska Wijayanti (Agrosains : Jurnal Penelitian Agronomi, 2017)
Arrowroot is a plant that potential to be one of the alternative food source for the community. The intensity of the light received by the plant is one of the influential factors important for plant growth. This study was conducted to determine the arrowroot plant growth analysis at different light. This research was conducted at the Experimental Farm Faculty of Agriculture, University of Sebelas Maret in Jumantono Karanganyar. This study uses a randomized block design Complete (RAKL) one treatment factor with four levels ie without shade, 31% shade, 51% shade and 73% shade. Data were analyzed by analysis of variance and if there is a significant difference continued with DMRT (Duncan Multiple Range Test) level of 5%. The results showed that the treatment of 51% shade known to give better growth results in some growth variables observed were plant height, leaf area index (LAI), segment length and chlorophyll contents.